2016
DOI: 10.3390/v8100269
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Studies towards Novel Modulators of Influenza A Virus–Host Interaction

Abstract: Human influenza A viruses (IAVs) cause global pandemics and epidemics. These viruses evolve rapidly, making current treatment options ineffective. To identify novel modulators of IAV–host interactions, we re-analyzed our recent transcriptomics, metabolomics, proteomics, phosphoproteomics, and genomics/virtual ligand screening data. We identified 713 potential modulators targeting 199 cellular and two viral proteins. Anti-influenza activity for 48 of them has been reported previously, whereas the antiviral effi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 163 publications
(127 reference statements)
0
16
0
Order By: Relevance
“…Viruses have evolved to evade the host antiviral response at various stages starting from viral sensing to antiviral pro-inflammatory responses (Bowie and Unterholzner 2008, Navratil et al 2011, Garcia-Sastre 2017. Multiple studies attempted to understand global principles of the viral evasion employed by various viruses, including dengue virus (DENV), Ebola virus (EBOV), IAV and HIV (Pichlmair et al 2012, Rozenblatt-Rosen et al 2012, Jäger et al 2011, Shah et al 2018, Batra et al 2018, Söderholm et al 2016. Global systems-level approaches including functional RNAi screens, interactome mapping technologies such as affinitypreprint purification mass spectrometry (AP-MS), quantitative proteomics and CRISPR/Cas9-based screens have provided unparalleled details and insights into the dynamics of host proteome in immune cells (Weekes et al 2014, Nightingale et al 2018, Kandasamy et al 2016, Ersing et al 2017), host-virus interactome (Pichlmair et al 2012, Rozenblatt-Rosen et al 2012, Jäger et al 2011, Shapira et al 2009, Konig et al 2010, and also identified important host dependency factors of various viruses (Shapira et al 2009, Marceau et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Viruses have evolved to evade the host antiviral response at various stages starting from viral sensing to antiviral pro-inflammatory responses (Bowie and Unterholzner 2008, Navratil et al 2011, Garcia-Sastre 2017. Multiple studies attempted to understand global principles of the viral evasion employed by various viruses, including dengue virus (DENV), Ebola virus (EBOV), IAV and HIV (Pichlmair et al 2012, Rozenblatt-Rosen et al 2012, Jäger et al 2011, Shah et al 2018, Batra et al 2018, Söderholm et al 2016. Global systems-level approaches including functional RNAi screens, interactome mapping technologies such as affinitypreprint purification mass spectrometry (AP-MS), quantitative proteomics and CRISPR/Cas9-based screens have provided unparalleled details and insights into the dynamics of host proteome in immune cells (Weekes et al 2014, Nightingale et al 2018, Kandasamy et al 2016, Ersing et al 2017), host-virus interactome (Pichlmair et al 2012, Rozenblatt-Rosen et al 2012, Jäger et al 2011, Shapira et al 2009, Konig et al 2010, and also identified important host dependency factors of various viruses (Shapira et al 2009, Marceau et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The vRNPs enter the nucleus through nuclear pore complexes [16]. In the nucleus viral genomic RNA is transcribed into positive-sense mRNA using viral polymerase [17,18]. The polymerase snatches 5' Caps from cellular RNA, performs RNA-dependent RNA polymerization and 3' RNA polyadenylation to make viral pre-mRNA.…”
Section: Iav Structure and Replication Cyclementioning
confidence: 99%
“…It also seems plausible that a public “data driven” approach for data mining, integration, and reuse would improve the ‘omics field by no small measure . Despite the individual merit of the various ‘omics based approaches, an integrative multi‐omics approach would provide a more robust outcome both in the discovery and validation phases of the ‘omics based biomarker pipeline . Very few dermatological review articles have focused on the application of ‘omics based approaches in human skin, and there remains a dearth of human hair proteomics reviews.…”
Section: ‘Omics Based Approaches For Hair Researchmentioning
confidence: 99%